Analysis on Line Follower Object Detecting Robot - S., Chaitanya Kumar; P., Kalyanasundaram (International Journal of Psychosocial Rehabilitation, 2020)
The line-following robot detects a visible line on a smooth area embedded in the ground and follows it. The trail line is predefined and visual, with a black line on the white area or the other. A line-follower robot is designed to develop and implement on a path of black on white or white on black using an IR sensor and an ultrasonic object detector. The Arduino coding is developed by using C programming. The proposed system is often implemented in schools, apartments, industries, and hospitals for security purposes.